Integrity amidst Schizophrenia - Jorge Carvalho (Joelho, 2015)
The fire, in 1988, that burned to the ground 14 buildings of Chiado, one of the areas in the 18th century Pombaline master plan for Lisbon downtown, created an unpredicted break in the history of this city. Álvaro Siza´s plan for the reconstruction of Chiado, seeks to preserve, through architecture, the cultural value of this area and to solve previously accumulated problems.